Velocidade excessiva nas vias urbanas de Belo Horizonte: prevalência e características associadas - Daniele Falci de Oliveira (2014)
Road accidents (RA) are important but neglected public health problem globally. Brazil ranks fifth place in RA mortality. For coping with this problem, the govermment has joined the Road Safety in 10 countries Project - R$ 10 (WHO / PAHO), deploying. The Vida no Tânsito Project on five state capitals for evaluation of interventions. The Urban Heath Observatory (OSUBH) was responsible for evaluating the impact of interventions in two cities , and Belo Horizonte (MG) city one of them. In 2012, the OSUBH conducted a roadside observational study aiming to estimate the prevalence of excessive speed on urban arterial roads (>60 km/h) and to study factors related to this behavior. The studied sample consisted of vehicles circulating in areas with and without fixed speed cameras in operation. Data were collected from 8565 vehicles, and cars were majority (72.0%); 40.0% of all vehicles observed at sites preceded 200 meters by radar and 33.6% in areas without radar (p<0.001) exceeded the local legal speed limits. The motorcycles had the highest average speed and the highest recorded speed (126 km/h). Men proved most among drivers (87.6%), cell phone use while driving was observed in 3.3% of drivers and 74.6% of them were using seat belt. In places without stationary radar, womem were observed using the phone more tham men (6,47% versus 2,71% p<0,05), independent of the speed limits. Female drivers used seatbelts more than males (88,89% versus 71,80% p <0,05) regardless whether they are within or above the speed limit and the presense or absence of fixed radars. The results suggest that adherence to compliance rules relating to speed limits an behavior change at individual and community level goes beyond structural interventions. The study contributes to the knowledge of risk factors and subsequent development of public policy strategies for reducing morbidity and mortality from RA in the context of a developing country.